TorrentU: uma arquitetura flexível para obtenção de informações sobre o universo de redes BitTorrent - Facchini, Giovani (Universidade do Vale do Rio do Sinos, 2009)
Recently, academic investigations mention the importance of peer-to-peer applications, mainly BitTorrent, focusing on studies published by internet providers as a source of information. Despite the importance of these collected data from internet providers, the studies behind this technique are limited in coverage, deepness, and, in some cases, do not show clarity in the method applied for retrieving the data. This work presents TorrentU, an scalable and flexible architecture for the observation of the BitTorrent universe. The main goal is to help on finding answers to a wide range of questions that has been raised regarding volume and types of files and content in BitTorrent networks.
Keywords: P2P; BitTorrent; Ciências Exatas e da Terra